Mapping Agricultural Research on Peatlands: A Bibliometric Analysis of Trends and Gaps (2004–2024) - Suhartawan, I Gede; Sulaiman, Zakia Putri (Kadiri University - Faculty of Agriculture, 2025)
Peatlands in Indonesia play a crucial role in global carbon storage and agricultural productivity. However, their use for agriculture has raised environmental concerns, particularly regarding land degradation, carbon emissions, and fire risks. This study employs a bibliometric approach using Publish or Perish (PoP) and VOSviewer to analyze research trends, dominant topics, and gaps in Indonesian peatland agriculture from 2004 to 2024. Three thousand nine hundred fifty (3,950) publications from Google Scholar were examined to identify thematic clusters and shifts in research focus. The results indicate a significant increase in research on peatland agriculture over the past two decades, with a primary focus on land management, environmental impact, and agricultural commodity adaptation. Oil palm remains the dominant research topic, while studies on alternative crops, horticulture, and sustainable peatland management strategies remain underexplored. Although fire mitigation has gained attention, long-term sustainability approaches and policy-driven land management strategies require further investigation. This study underscores the need for a multidisciplinary and collaborative approach to ensure sustainable peatland agriculture. Future research should prioritize the diversification of peat-adaptive crops, precision agriculture technologies, and ecosystem-based restoration methods. Additionally, policymakers must integrate research findings into comprehensive land-use planning to balance agricultural productivity with environmental conservation. Strengthening regulations, incentivizing sustainable practices, and fostering interdisciplinary collaboration will be essential for addressing the challenges of peatland agriculture and ensuring its long-term viability.